INTERNATIONAL RELATION AS THE BASIC PART OF WORLD POLICY - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analizes the assence of international relations, its transformation in modern world. The basic paradigm of nature and character of international relations are revieled.